Reversible Switching between Highly Porous and Nonporous Phases of an Interpenetrated Diamondoid Coordination Network That Exhibits Gate‐Opening at Methane Storage Pressures. Issue 20 (17th April 2018) - Yang, Qing‐Yuan; Lama, Prem; Sen, Susan; Lusi, Matteo; Chen, Kai‐Jie; Gao, Wen‐Yang; Shivanna, Mohana; Pham, Tony; Hosono, Nobuhiko; Kusaka, Shinpei; Perry, John J.; Ma, Shengqian; et al.
Abstract: Herein, we report that a new flexible coordination network, NiL2 (L=4‐(4‐pyridyl)‐biphenyl‐4‐carboxylic acid), with diamondoid topology switches between non‐porous (closed) and several porous (open) phases at specific CO2 and CH4 pressures. These phases are manifested by multi‐step low‐pressure isotherms for CO2 or a single‐step high‐pressure isotherm for CH4 . The potential methane working capacity ofNiL2 approaches that of compressed natural gas but at much lower pressures. The guest‐induced phase transitions ofNiL2 were studied by single‐crystal XRD, in situ variable pressure powder XRD, synchrotron powder XRD, pressure‐gradient differential scanning calorimetry (P‐DSC), and molecular modeling. The detailed structural information provides insight into the extreme flexibility ofNiL2 . Specifically, the extended linker ligand, L, undergoes ligand contortion and interactions between interpenetrated networks or sorbate–sorbent interactions enable the observed switching. Abstract : A new flexible coordination network, NiL2 (L=4‐(4‐pyridyl)‐biphenyl‐4‐carboxylic acid), undergoes extreme structural transformations, enabled by ligand contortion, between non‐porous (closed) and porous (open) phases as exemplified by a stepped isotherm.